TAK-442, a Direct Factor Xa Inhibitor, Inhibits Monocyte Chemoattractant Protein 1 Production in Endothelial Cells via Involvement of Protease-Activated Receptor 1 - Shinozawa, Emiko; Nakayama, Masaharu; Imura, Yoshimi (Frontiers in Pharmacology, 2018)
Oral blood coagulation inhibitors and their receptors, such as factor Xa (FXa), thrombin, and the thrombin receptor protease-activated receptor 1 (PAR1), are entered into clinical trials for acute coronary syndrome therapy; however, the results obtained so far are different for each drug. The underlying mechanisms of the results have not been fully investigated. We studied the in vitro anti-inflammatory effects of the selective FXa inhibitor TAK-442 on human endothelial cells, with comparing those of the selective thrombin inhibitor melagatran and the PAR1 antagonist vorapaxar. In human umbilical vein endothelial cells, FXa-increased production of monocyte chemoattractant protein 1 (MCP-1), a key inflammatory mediator, was inhibited by TAK-442 but not melagatran, and was also remarkably suppressed by vorapaxar. As thrombin did, FXa increased calcium mobilization in PAR1-overexpressed Chinese hamster ovary cells, which was selectively inhibited by TAK-442 and vorapaxar. We therefore confirmed the inhibitory effect of TAK-442 in endothelial MCP-1 production and the PAR1 intervention in the response. Our results suggest that TAK-442 may have anti-inflammatory potential in addition to its anti-thrombotic effects.